50 favorite rooms by Frank Lloyd Wright - Maddex, Diane (New York: Smithmark Publishers, 1998)
Wright was one of the world's favourite architecht
Includes index
Keywords: Interior architechture -- United States; Room layout (Dwellings) -- United States